2013
DOI: 10.1002/ijc.28490
|View full text |Cite
|
Sign up to set email alerts
|

Influence of omega‐3 fatty acids on Tamoxifen‐induced suppression of rat mammary carcinogenesis

Abstract: We report here a detailed time course study of the individual and combined chemopreventive effects of Tamoxifen (Tam) and a high fish oil (FO) diet on multiple histologic parameters of mammary carcinogenesis. Groups of female Sprague-Dawley rats were injected ip with 1-methyl-1-nitrosourea at 50 days of age and assigned to either a control diet (20% corn oil [CO]) or a FO-rich diet (10% FO + 10% CO) in the presence and absence of Tam in the diet (0.6 ppm). Rats were sacrificed at weeks 4 (before palpable tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 16 publications
(54 reference statements)
0
14
1
1
Order By: Relevance
“…Because such compounds are to be used in healthy women, they have to be safe without significant side effects. Our preclinical data in rodent models of mammary carcinogenesis have shown that fish oil, rich in omega-3FA, potentiated the chemopreventive effect of tamoxifen (5,6). Furthermore, our signaling (7), genomic (8), and proteomic (9) studies suggested complementarity in the mechanism of antitumor action of tamoxifen and n-3FA.…”
Section: Introductionmentioning
confidence: 60%
“…Because such compounds are to be used in healthy women, they have to be safe without significant side effects. Our preclinical data in rodent models of mammary carcinogenesis have shown that fish oil, rich in omega-3FA, potentiated the chemopreventive effect of tamoxifen (5,6). Furthermore, our signaling (7), genomic (8), and proteomic (9) studies suggested complementarity in the mechanism of antitumor action of tamoxifen and n-3FA.…”
Section: Introductionmentioning
confidence: 60%
“…mega-3 PUFAs signaling via GPR120 and Toll-like receptor 4 (TLR4) utilize the same NFκB and JNK pathways as TNFα so they could potentially interfere with these proliferative signals 19 , 34 . Among dietary fat subtypes, ω-3 PUFAs offer the most promise for reducing the risk of carcinogenesis 18 , 21 . So we tested whether HFD supplementation with ω-3 PUFAs derived from fish oil (FOD, fish oil diet) could reduce inflammation in the mammary and perigonadal fat pads of obese OVX mice in the absence of tumor formation.…”
Section: Resultsmentioning
confidence: 99%
“…It is perceived that the observed effects may be attributed to their influence on gene expression, transcription factors, and suppression of neoplastic stimulations, and to their ability to influence the production of ROS, cell metabolism and induce apoptosis (24,25,26). Fatty acids were also shown to enhance the effectiveness of standard chemo-or radiotherapy (27,28). On the contrary, SFA and MUFA can stimulate tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%